Imaging Osteomyelitis: An Update - Aydingoz, Ustun (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2023)
Background Hematogenous osteomyelitis has increased over the past quarter century in frequency, virulence, and degree of soft-tissue involvement, bringing about changes in clinical manifestations and management of the disease especially in children that should be reflected in the current imaging approach. Likewise, the global disease burden of diabetes has increased greatly in the same period, compounding the problem of ascertaining osteomyelitis in diabetic foot.Method This article provides an updated overview of imaging findings in hematogenous and contiguous osteomyelitis based on the literature and our institutional experience, along with salient features of recent recommendations from expert groups on the diagnostic algorithms and reporting terminology.Results and Conclusion Findings on radiography and especially magnetic resonance imaging (MRI) closely reflect pathophysiology in osteomyelitis, whereby the characteristic involvement of the metaphysis or metaphyseal-equivalents, the formation and subperiosteal extension of intramedullary pus collection, and the development of cloaca, sequestrum, and involucrum are all diagnostic clues. Non-enhancing foci within the medullary bone, the penumbra sign, intra- or extramedullary fat globules, and surrounding soft tissue inflammation or abscesses are among key MRI findings. Diabetic foot is a special condition with characteristic pathophysiologic and imaging features that suggest the likelihood of osteomyelitis and the main differential diagnostic consideration of acute on chronic neuropathic osteoarthropathy with or without osteomyelitis.Key Points Citation Format
Keywords: bones; infection; MR imaging